Elbow Arthrodesis Using a Medially Positioned Plate in 6 Dogs - McCarthy, Jessica; Comerford, Eithne J.; Innes, John F.; Pettitt, Rob A. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to report the surgical technique, associated complications and clinical outcome of elbow arthrodesis using a medially positioned plate.Study Design This was a retrospective case series.Results Six cases met the inclusion criteria. In all cases, the elbow was approached medially without the requirement for ulnar osteotomy. A non-locking 2.7/3.5- mm pre-contoured elbow arthrodesis plate was applied in 5/6 cases and a 2.0-mm String of Pearls plate applied in one case. The mean angle of arthrodesis was 118° (range: 113–130°). One major intraoperative complication occurred. Three minor and 3 major postoperative complications occurred. Postoperative imaging was available for 5/6 cases. Complete arthrodesis was confirmed by imaging in 4/5 cases, partial progression of arthrodesis was documented in 1/5 cases and no further images were deemed necessary. Postoperative Liverpool Osteoarthritis in Dogs score was available for two cases with scores of 20/52 and 10/52, respectively. Subjective outcomes in the remaining three cases were rated as acceptable more than 1 year postoperatively.Conclusion Positioning the plate medially for elbow arthrodesis simplified the surgical approach, could be performed with a pre-contoured plate and allowed successful revision of an arthrodesis previously stabilized with a caudally positioned plate. The cases in this series had acceptable outcomes despite a high risk of complications.
Keywords: elbow; arthrodesis; medial plate; angle of arthrodesis; outcome of elbow arthrodesis; dogs